Identifikasi Pemborosan Dengan Pendekatan Lean Warehouse Pada Gudang Oli di PT ABC - Ardysti, Amelia Ramadhani; Ernawati, Dira (BRILIANT: Jurnal Riset dan Konseptual, 2025)
Warehouses have an important role because they influence operational activities in a company's business processes. PT. ABC is one of Pertamina's official distributors which is engaged in logistics and distribution activities for oil, fuel, and heating products. In carrying out its operational activities, PT. ABC is still faced with various problems. The occurrence of delivery delays due to waiting times that are too long is the main problem at PT. ABC. Therefore, this research aims to identify waste and provide recommendations for improvements to warehousing activities. The lean warehouse approach is used to identify and eliminate waste through value stream mapping and process activity mapping tools. The research results were obtained through predictions of the proposed improvement recommendations, where it can be seen that the highest type of waste is waiting. After the proposed improvements, warehousing activity time decreased from 526 minutes to 355 minutes. In addition, the overall efficiency of warehousing activities increased by 22.14%, from the previous 47.72% to 69.86%.